2002
DOI: 10.1108/eb037966
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Feedback on the Relationship Between Budgetary Participation and Performance

Abstract: Access to this document was granted through an Emerald subscription provided by emerald-srm: 463575 [] For AuthorsIf you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which Downloaded by UNIVERSITY OF EXETER At 13:18 16 August 2015 (PT)publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 45 publications
0
14
0
1
Order By: Relevance
“…Beberapa penelitian membuktikan bahwa partisipasi penyusunan anggaran mempunyai efek positif terhadap kinerja manajerial, yaitu: Kenis (1979); Merchant (1981); Frucot and Shearon (1991); Yusfaningrum dan Ghozali (2005), Etemadia et al (2009), Yahya et al (2008), Damayanti (2007), Sinuraya (2009) dan Tangkau (2009). Penelitian lainnya menunjukkan hasil tidak signifikan yaitu penelitian Chong and Chong (2002), Brownell and Hirst, (1986) dimana Mereka menemukan hasil yang tidak signifikan antara partisipasi penyusunan anggaran dengan kinerja manajerial, hal ini terjadi karena hubungan partisipasi penyusunan anggaran dengan kinerja manajerial tergantung pada faktor-faktor situasional atau lebih dikenal dengan istilah variabel kontigensi (Contigency Variabel).…”
Section: Pendahuluanunclassified
“…Beberapa penelitian membuktikan bahwa partisipasi penyusunan anggaran mempunyai efek positif terhadap kinerja manajerial, yaitu: Kenis (1979); Merchant (1981); Frucot and Shearon (1991); Yusfaningrum dan Ghozali (2005), Etemadia et al (2009), Yahya et al (2008), Damayanti (2007), Sinuraya (2009) dan Tangkau (2009). Penelitian lainnya menunjukkan hasil tidak signifikan yaitu penelitian Chong and Chong (2002), Brownell and Hirst, (1986) dimana Mereka menemukan hasil yang tidak signifikan antara partisipasi penyusunan anggaran dengan kinerja manajerial, hal ini terjadi karena hubungan partisipasi penyusunan anggaran dengan kinerja manajerial tergantung pada faktor-faktor situasional atau lebih dikenal dengan istilah variabel kontigensi (Contigency Variabel).…”
Section: Pendahuluanunclassified
“…Lau and Ng (2003) investigate the moderating effect of organisational commitment in the association between performance evaluation style and budgetary participation. Chong and Chong (2002) further examine the moderating effect of feedback on the relationship between budgetary participation and performance. Finally, Lau (2001) investigate how the emphasis on tight budget and cost control interact with the budgetary performance.…”
Section: Introductionmentioning
confidence: 99%
“…If they reckon that participating in budgeting (the behaviour) will improve their performance (specific goal), then they will participate more. Going by the interaction between budgetary participation and managerial performance as documented in extant literature [Agbejule & Saarikoski, 2006;Frucot & White, 2006;Chong & Chong, 2002;Nouri & Parker, 1998;Brownell & McInnes, 1986], it is hypothesized that:…”
Section: Vroom's Expectancy Theorymentioning
confidence: 99%
“…The judicious utilisation of financial resources in such public sector organisations, facilitated by the existence of a sound budgeting system, could translate directly to the efficient utilisation of state resources. Review of literature on budgetary participation (BP) and managerial performance (MP) reveals a leaning towards private sector organisations in comparison to the public sector organisations [see Milani, 1975;Brownell & McInnes, 1986;Nouri & Parker, 1998;Chong & Chong, 2002;Agbejule & Saarikoski, 2006;Frucot & White, 2006;Yuen, 2007;Adeyeye, Otusanya & Uadiale, 2013]. In contributing to the debate on budgetary participation and managerial performance in public sector organisations, Thomson (1967) (cited in Williams, Macintosh & Moore, 1990), suggested that budgetary behaviour in private sector organisations may be different from public sector settings, thus suggesting limitation in the scope of generalisability of empirical results from budgetary participation and managerial performance in the private sector organisation, hence the need for study of public sector organisations.…”
Section: Introductionmentioning
confidence: 99%